The Influence of Leading Sectors on Poverty Alleviation Towards Inclusive Development In Central Lombok District - Khalqi, Izhar (UIN Mataram, 2024)
Poverty in Central Lombok Regency in 2020 was recorded at 13.44 percent. When compared with districts/cities in West Nusa Tenggara Province, the percentage of poor people in Central Lombok Regency is in the fifth lowest position from the first position of North Lombok Regency 26.99 percent, East Lombok Regency 15.24 percent, Bima Regency 14.49 percent and West Lombok Regency 14.28 percent. Leading sectors are expected to be able to overcome economic development problems such as poverty levels, because poverty is a major aspect in the success of economic development. By knowing the leading sectors can have an influence on the rate of growth of the Gross Regional Domestic Product of Central Lombok Regency, it can assist the government in managing policies in terms of economy and regional development so that the poverty rate in Central Lombok Regency can be reduced. This research is a quantitative study with the type of data used in this study is secondary data obtained from the Central Statistics Agency of Central Lombok Regency and the Central Statistics Agency of West Nusa Tenggara Province. The independent variable of this research is the growth of the leading sectors in Central Lombok Regency and the dependent variable in this research is the poverty level of Central Lombok Regency.